2014
DOI: 10.1016/j.jhealeco.2014.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Parental health and child schooling

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 55 publications
1
36
3
1
Order By: Relevance
“…Previous studies have also shown that parental health is correlated with offspring health (Modin et al 2009), which can in turn influence socioeconomic outcomes (Adler and Ostrove 1999). Furthermore, parental health can have a direct influence on offspring socioeconomic outcomes (Bratti and Mendola 2014). This previous research suggests that parental SES and parental health are likely to be confounding factors for the relationship between birth interval length and long-term educational, cognitive, and socioeconomic outcomes for the offspring.…”
Section: Empirical Research On the Long-term Effects Of Birth Intervalsmentioning
confidence: 99%
“…Previous studies have also shown that parental health is correlated with offspring health (Modin et al 2009), which can in turn influence socioeconomic outcomes (Adler and Ostrove 1999). Furthermore, parental health can have a direct influence on offspring socioeconomic outcomes (Bratti and Mendola 2014). This previous research suggests that parental SES and parental health are likely to be confounding factors for the relationship between birth interval length and long-term educational, cognitive, and socioeconomic outcomes for the offspring.…”
Section: Empirical Research On the Long-term Effects Of Birth Intervalsmentioning
confidence: 99%
“…However, many transition governments did not maintain this positive feature, allowing the human capital advantage to dissipate due to weak public investment in education [1], [2], [3], [4]. Several studies show that different household-level shocks further hampered children's educational success, forced children to drop out of school [3], [5], [6], [7], or increased their probability of suffering from depression or other health problems [8]. Transition shocks also reduce the presence of parents in the household and the time they are able to devote to their children [9].…”
Section: Motivationmentioning
confidence: 99%
“…Among the most influential factors are the civil wars that occurred in the former Yugoslavia, Albania, and Tajikistan in the 1990s. A study on BiH explores the nexus between civil wars and children's educational attainment in the long term [5]. It focuses on the role parental health plays in children's schooling (health outcomes after the war were below those of other countries in the region).…”
Section: Parental Health and Children's Human Capital Developmentmentioning
confidence: 99%
“…Poor mental health may entail poor labour market conditions, income losses, and higher health expenses (Miranda and Patel, 2005). Studies of individual behaviour have documented the impact of mental health on employment, productivity and earnings (Ettner et al 1997;Bartel and Taubam, 1986), criminal activity (Steadman et al 1998), child abuse and neglect (Kelleher et al, 1994), homelessness (Jenks, 1994), fertility and divorce (Bartel and Taubman, 1986), and offspring's education (Bratti and Mendola, 2014). Emerging data from low-and middle-income countries further indicate a strong association between mental illness and low education, food insecurity, inadequate housing, poverty and financial stress (Das et al 2008;Patel and Kleinman 2003).…”
Section: Exposure To Violence and Mental Health: A Brief Literature Rmentioning
confidence: 99%